Passive distance measurement using low power light emitting diode - Nor Nazirah, Saidon (2018)
There are many types of distance measurement sensor available in market that is used in various applications such as in robotics field and also in manufacturing industries. A low cost and high accuracy of the device are important in most of the applications lead to various types of distance measurement methods. Furthermore, a large number of literatures prove that searching for other methods of measuring distances is intentional, especially for sensory applications and a high interest is observed in non-contact measurement techniques. This thesis is about distance measurement system using a low cost and less power consumption of light emitting diode (LED). In this project, a passive distance measurement technique is applied and an object with flat surface is created from monochromatic light source in a controlled illumination level of surrounding that is used for image processing.